Apoptosis Neuron Nukleus Merah pada Tikus Model Penyakit Parkinson Akibat Induksi Parakuat Diklorida - Khasanah, Ayu Miftahul; Fahma, Niswah Nurul; Pangestiningsih, Tri Wahyu (Jurnal Veteriner, 2020)
Red nucleus plays a role in motoric control, so that disturbanced of neurons in this nucleus could be affected on motor impairment. Previous study reported that paraquat (PQ) could induced Parkinson disease, a neurodegeneratif disease that affected subtantia nigra pars compactca and clinically characterized by motoric disorders. Apoptosis is a programed cell death that physiologically normal for the body, but in large quantities will cause progresive cell death. This study aimed to observed apoptosis in rats RN neurons following by PQ injection. Ten male Wistar rats with the aged of 3 month, devided into two groups of five. Control group was given aquadest and treatment group was given PQ, injected intraperitoneally, dosage 7 mg/kg BW, twice a week for three weeks. At day 24 th all rats were anesthetized using ketamin dosage 40 mg/kg BW and xylazine dosage 5 mg/kg BW, perfused intracardially using 4% paraformaldehyde and mesencephalons were collected. Mesencephalons were processed for histological preparations using the paraffin method and cut stereologically in coronal section, in 4 ?m thickness. Immunohistochemistry staining was done using caspase 3 antibody as a marker of apoptosis. Data were analyzed descriptively    and quantitatively. The results in both groups showed RN neurons were large size and stelat or fusiform in shape. The percentage of apoptotic neurons in the RN of treatment group was significantly increased (80,4%±13,8%) compared to the control group (26,6%±18,32%) (P<0.01). In conclusion, following PQ exposure there is a significant increased of apoptosis neurons number in the RN of rat model of Parkinson disease.